Analysis of the Release of Medical Record Information as a Guarantee of Legal Aspects of Patient Data Confidentiality: Analisis Pelepasan Informasi Rekam Medis sebagai Penjamin Aspek Hukum Kerahasiaan Data Pasien - Setyaningsih, Fahmi; Meylia, Nadira Zalfa; Mayasari, Winda Nur; Parmesti, Khoirunnisa Riski; Wahyudi, Rusli Diki; Indira, Zahrasita Nur; Siregar, Rahmadhani (Universitas Muhammadiyah Sidoarjo, 2025)
Medical records are certainly very close to maintaining the security and confidentiality of patient data in the means of releasing information by ensuring the legal aspects of the security and confidentiality of patient data. Maintaining the security and confidentiality of patient data during the process of releasing medical record file information is very important in order to facilitate access to information on lawsuits by health services and health practitioners, as well as authorized third parties. This study aims to provide an overview of the release of medical record information in the legal aspect of confidentiality. The things that were studied were the procedures for releasing medical record information, the requirements for releasing medical information, the parties involved in releasing medical information, information on the use of releasing medical information and looking at the security aspects of the process of releasing medical record information, as well as facilities and infrastructure in the information release room. The data collection methods used in this study were interviews and observations. The results of the research on the process of releasing medical information show that two patients are in accordance and two patients are not in accordance with the SOP (Standard Operating Procedure) that applies at JIH Purwokerto Hospital, the human resources involved in the process of releasing information are Medical Recorder and Health Information (PMIK) officers and non PMIK, and inadequate facilities and infrastructure available in the information release room.